Publicizing Arbitrage - Kahraman, Bige (Journal of Financial and Quantitative Analysis, 2021)
Abstract How does greater public disclosure of arbitrage activity and informed trading affect price efficiency? To answer this, we exploit rule amendments in U.S. securities markets, which impose a higher frequency of public disclosure of short positions. Higher public disclosure can hurt the production of information and deteriorate efficiency, or it can be beneficial by mitigating the limits to arbitrage and diffusing arbitrageurs’ information faster. With more frequent disclosure, information encapsulated within short interest is incorporated into prices faster, improving price efficiency. We find important reductions in short sellers’ horizon risk and increases in short sales with the rule amendments.